A Comparison Analysis Of Ahp And Topsis Methods In The Selection Of Outstanding Students At Smp Negeri 5 Kaur Of Bengkulu Province - Dewi Murniati; Asnawati Asnawati; Rizka Tri Alinse (Jurnal Media Computer Science, 2022)
The number of decision support system methods makes it difficult for decision makers to determine which method is better to use in a case. In this case is the selection of outstanding students at SMP Negeri 5 Kaur of Bengkulu Province. The decision support system method taken for comparison is AHP and TOPSIS methods. In helping the comparison process, an application for selecting outstanding students at SMP Negeri 5 Kaur of Bengkulu Province was built using the Visual Basic.Net programming language and SQL Server 2008r2 database. A comparative analysis is done by looking at 2 aspects, namely the final result of the assessment and the processing time. Based on the final results of the assessment, AHP and TOPSIS methods have different results, this is because there are differences in determining the weight of the criteria, where AHP method is obtained from the results of pairwise comparisons while TOPSIS method is obtained from the school. Based on the processing time, AHP method is faster than TOPSIS method, this is because the stages in the AHP method process are fewer than the TOPSIS method